Fish Larval Assemblage Associated with an Eastern Tropical Pacific Coral Reef: Seasonal and Interannual Variability - Juan José Gallego-Zerrato; Diego Fernando Córdoba-Rojas; Alan Giraldo (Diversity)
The seasonal and interannual temporal variation in the composition, richness, diversity, and similarity of fish larval assemblages associated with an Eastern Tropical Pacific (ETP) coral reef system was studied in March (cold water) and September (warm water) during the years 2017, 2018, and 2019. Throughout the study period, we collected 4779 fish larvae and identified 88 taxa, encompassing 46 families. This increased the total number of recorded fish taxa for the region to 146. Fish larvae were collected by daytime and nighttime surface trawls, using a bongo net 30 cm in diameter and 180 cm in length, equipped with mesh sizes of 300 and 500 μm. The species diversity and abundance of ichthyoplankton over this ETP coral reef changed by intra-annual variation of the hydrological conditions of the upper layer of the sea. Six significant assemblages were identified (SIMPROF, p < 0.05), each one associated with each sampling period (ANOSIM, R = 0.764); Cetengraulis mysticetus, Diaphus pacificus, Anchoa sp., Anisotremus sp., Bremaceros bathymaster, Oligoplites saurus, Caranx sp., Seriola sp., Gobiidae sp., Microgobius sp., and Synodus evermanni were the species that contributed to dissimilitude between groups. Canonical correspondence analysis revealed significant associations between specific larval fish taxa abundance and temperature, salinity, dissolved oxygen, and zooplankton biomass. Overall, the assemblage of ichthyoplankton in this ETP coral reef system is sensitive to seasonal changes in water column hydrographic conditions.